2017
DOI: 10.1186/s12955-017-0643-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life among adolescents and young adults with a bleeding disorder

Abstract: BackgroundHealth-related quality of life (HRQoL) in adolescents and young adults with bleeding disorders is under-researched. We aimed to describe factors related to HRQoL in adolescents and young adults with hemophilia A or B or von Willebrand disease.MethodsA convenience sample of volunteers aged 13 to 25 years with hemophilia or von Willebrand disease completed a cross-sectional survey that assessed Physical (PCS) and Mental (MCS) Component Summary scores on the SF-36 questionnaire. Quantile regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 45 publications
0
39
3
4
Order By: Relevance
“…Variables found to be significantly associated with HRQOL are gender, participation in sports and school attendance. A recent study in the United States on predictors of HRQOL in adolescents with CBD also found gender associated with HRQOL . Boys reporting higher HRQOL than girls have been demonstrated in (healthy) populations and partially explain the influence of gender on HRQOL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Variables found to be significantly associated with HRQOL are gender, participation in sports and school attendance. A recent study in the United States on predictors of HRQOL in adolescents with CBD also found gender associated with HRQOL . Boys reporting higher HRQOL than girls have been demonstrated in (healthy) populations and partially explain the influence of gender on HRQOL.…”
Section: Discussionmentioning
confidence: 90%
“…Boys reporting higher HRQOL than girls have been demonstrated in (healthy) populations and partially explain the influence of gender on HRQOL. In addition, as mentioned earlier, the HRQOL of girls with CBD may be affected by heavy menstruations, and it is possible that this has a more immediate detrimental effect on HRQOL than the long‐term effects (eg arthropathy) associated with haemophilia, which may have not yet fully manifested in this population …”
Section: Discussionmentioning
confidence: 99%
“…La intensidad del dolor es el principal factor influyente en el nivel de calidad de vida física y psicológica de los pacientes con hemofilia, razón por la que el alivio clínico del mismo y el mantenimiento del bienestar físico es crucial para el mantenimiento de una buena CVRS [12,21]. Este síntoma se presenta en mayor proporción en los pacientes con hemofilia severa, sin embargo, también es un hallazgo de importancia en la hemofilia leve a moderada que se debe tener en cuenta durante el abordaje.…”
Section: Generalidades De La Hemofilia Presentación Clínicaunclassified
“…La calidad de vida de los pacientes con hemofilia presenta variación con la edad, ya que a medida que se envejece cambian las preferencias y necesidades de los pacientes [16,21]. Se ha descrito que, para la población pediátrica con hemofilia, el principal determinante para una buena calidad de vida se compone de las amistades, familia y el tratamiento, mientras que, para la población adolescente son la actividad física, el apoyo percibido y la escuela.…”
Section: Determinantes Según La Edadunclassified
See 1 more Smart Citation